2008
DOI: 10.1073/pnas.0801773105
|View full text |Cite
|
Sign up to set email alerts
|

AP4 encodes a c-MYC-inducible repressor of p21

Abstract: In the majority of human tumors, expression of the c-MYC oncogene becomes constitutive. Here, we report that c-MYC directly regulates the expression of AP4 via CACGTG motifs in the first intron of the AP4 gene. Induction of AP4 was required for c-MYCmediated cell cycle reentry of anti-estrogen arrested breast cancer cells and mitogen-mediated repression of the CDK inhibitor p21. AP4 directly repressed p21 by occupying four CAGCTG motifs in the p21 promoter via its basic region. AP4 levels declined after DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
191
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(209 citation statements)
references
References 47 publications
17
191
0
Order By: Relevance
“…It indicates that AP4 may play a dual role in cell proliferation via different pathways. Similar to our results, AP4 has been reported to promote cell growth in HCC [41], colorectal carcinoma [42] and gastric cancer [43]. Moreover, it has been proposed that AP4 could activate cell migration and EMT mediated by p53 in MDA-MB-231 cells [44] and mediate a c-MYC-induced EMT in colorectal cancer [45].…”
supporting
confidence: 79%
See 1 more Smart Citation
“…It indicates that AP4 may play a dual role in cell proliferation via different pathways. Similar to our results, AP4 has been reported to promote cell growth in HCC [41], colorectal carcinoma [42] and gastric cancer [43]. Moreover, it has been proposed that AP4 could activate cell migration and EMT mediated by p53 in MDA-MB-231 cells [44] and mediate a c-MYC-induced EMT in colorectal cancer [45].…”
supporting
confidence: 79%
“…Interestingly, it has been shown that c-MYC could directly regulate AP4 expression and c-MYC-AP4-p21 cascade plays an important role in maintaining cells in a proliferative, progenitor-like state of HCC and colorectal carcinoma [41,42]. Taken together, these results suggest that c-MYC-AP4-LAPTM4B-c-MYC axis may form a feedback loop to participate in cell growth and metastasis.…”
supporting
confidence: 55%
“…c-Myc directly regulates the expression of AP4 via CACGTG motifs in the first intron of the AP4 gene, and AP4 directly represses p21 expression by occupying four CAGCTG motifs in the p21 promoter (Figure 6b). 37 These findings indicate that c-Myc protein downregulates p21 expression (Figure 6e). …”
Section: Dnmt-1 Controls the C-myc Expression And The Upregulation Ofmentioning
confidence: 75%
“…It has been reported that TFAP4 controls the expression of numerous genes regulating cell proliferation (2,3). TFAP4 target genes also include stem cell markers such as LGR5 and regulators of epithelial-mesenchymal transition such as SNAIL and E-cadherin (2,3).…”
mentioning
confidence: 99%
“…Transcription factor activating enhancer-binding protein 4 (TFAP4) 3 is a ubiquitously expressed basic helix-loop-helix leucine-zipper transcription factor that binds to the consensus E-box sequence 5Ј-CAGCTG-3Ј (1). It has been reported that TFAP4 controls the expression of numerous genes regulating cell proliferation (2,3).…”
mentioning
confidence: 99%